2021
DOI: 10.1002/fsn3.2425
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of natural pigments produced by Monascus purpureus in submerged fermentation

Abstract: Color is one of the most important characteristics of foods. It includes visual signals for flavor identification and taste thresholds. Furthermore, color plays significant roles in consumer satisfaction of foods (Hutchings, 2021). Legally permitted pigments are divided into two major categories of natural and synthetic.Natural colors include beneficial and therapeutic characteristics.Use of natural colors is one of the current marketing trends because of consumer's concerns about the safety of artificial food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The (ii) submerged fermentation that are the microorganisms growing in a liquid medium with nutrients, which demonstrates the ease of homogenization and process control such as oxygenation, pH, and temperature (Agboyibor et al, 2019;Chai et al, 2020;Abdollahi et al, 2021;Abuthahir et al, 2021;Chen et al, 2021;de Almeida et al, 2021). In addition, the pigments are secreted into the fermentation medium and then recovered in a separation step, such as centrifugation or using simple solvent extraction (Lemes et al, 2021).…”
Section: Monascus Sp and Its Pigment Production Potentialmentioning
confidence: 99%
See 3 more Smart Citations
“…The (ii) submerged fermentation that are the microorganisms growing in a liquid medium with nutrients, which demonstrates the ease of homogenization and process control such as oxygenation, pH, and temperature (Agboyibor et al, 2019;Chai et al, 2020;Abdollahi et al, 2021;Abuthahir et al, 2021;Chen et al, 2021;de Almeida et al, 2021). In addition, the pigments are secreted into the fermentation medium and then recovered in a separation step, such as centrifugation or using simple solvent extraction (Lemes et al, 2021).…”
Section: Monascus Sp and Its Pigment Production Potentialmentioning
confidence: 99%
“…Once produced, pigments need to be properly obtained, separated, and identified, since their value and application are directly related to purity degree (Mukherjee and Singh, 2011) and stability, which can be affected by factors such as light, oxygen, and metal ions presence, pH levels, as well as high temperatures (Vendruscolo et al, 2016;Abdollahi et al, 2021). Separation methods vary according to the location of the pigment (intracellular or extracellular) production and the need for use for each application.…”
Section: Monascus Sp and Its Pigment Production Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinetic models of pigment stability are also a useful tool to evaluate the pigment behavior when exposed to extreme conditions, thereby, assessing feasible solutions to enhance their stability (Liu et al, 2022). In fact, in a recent study, by applying a response surface methodology, the authors have observed higher stability of Monascus-derived pigments in lower temperatures (60ÚC -75ÚC) unless the pH was adjusted to 7 which enables the pigment stabilization in higher temperature range (75ÚC -88ÚC) (Abdollahi et al, 2021).…”
Section: Evaluation Of the Stability Of The Produced Biopigmentsmentioning
confidence: 99%